Characterisation of vaginal Prevotella strains from a cohort of South African adolescent girls and young women with and without bacterial women with and without bacterial vaginosis - Welp, Kirsten (Department of Pathology, 2025)
A common condition in reproductive age women, bacterial vaginosis (BV), is characterised by a dysbiosis in the vaginal microbiome, and frequently associated with abundance of the genus Prevotella. Prevalence of BV is particularly high in sub-Saharan Africa and comprehensive characterisation of South African BV-associated bacteria is vital for BV management in the region. However, to date, most research has focussed on BV-associated Prevotella species from the global North. A total of 69 Prevotella isolates were purified from vaginal samples from the UChoose cohort study, which was designed to assess the effect of hormonal contraceptives on HIV risk in adolescent girls and young women (16-19 years old). Isolate genus was confirmed by Prevotella genus-specific PCR for all isolates. A subset was speciated by 16S rRNA gene sequencing to be P. bivia (n=36) and a putative P. melaninogenica (n=1) and were carried forward for further phenotypic characterisation, including antimicrobial resistance testing by Etest methodology, and quantification of biofilm formation by crystal violet staining. South African Prevotella isolates displayed 2.7% and 8.3% resistance to metronidazole and clindamycin, respectively, with higher rates of resistance against non-BV antibiotics (19.44%-38.89%). Several strains exhibited co- resistance to two (12/36), three (6/36) or four (2/36) antibiotics. Biofilm formation was significantly greater than the P. bivia ATCC 29303T type-strain in over a quarter of strains (p>0.05), with some intra-sample diversity in biofilm-forming ability. Additionally, 36 strains (35 P. bivia and 1 P. melaninogenica) were whole genome sequenced using Illumina MiSeq technology. Genomes of these isolates, and of published sequences on the NCBI RefSeq database, were annotated and screened for antimicrobial resistance and virulence genes, as well as for the presence of prophages or anti-phage defence mechanisms. Phylogenetic analysis by cpn60 gene sequencing and core genome alignment revealed that intra-sample diversity was generally low, but at least one sample had two distinct strains at the same time point. The putative P. melaninogenica isolate was most closely related to another vaginal Prevotella spp., but both were potential novel species based on average nucleotide identity score (<95%). Isolation location (South African versus international) was not reflected in the phylogenetic trees and there were no differential genes associated with isolate origin. Antimicrobial resistance genes relevant to metronidazole (nimK) and clindamycin resistance (ermF) were identified in 2.27% (1/44) and 29.09% (4/44) strains, respectively. The variants of the β-lactamase gene, cfxA, were differentially associated with resistance to a β-lactam antibiotic (p=0.000212). Lipopolysaccharide (LPS) production was assessed in a subset of Prevotella strains using a commercially available isolation and quantification kit. LPS production was 24-fold higher in the P. melaninogenica-related strain, compared to five P. bivia isolates tested (p<0.05), and was structurally different to P. bivia LPS as observed by SDS-PAGE. Overall, isolates, added to a Prevotella biorepository, were phenotypically and genotypically characterised, which will enable regionally relevant BV research into future intervention and treatment plans.